Prevalence of presumed ocular tuberculosis among pulmonary tuberculosis patients in a tertiary hospital in the Philippines - Lara, Leon Paolo R (Springer, 2013)
BACKGROUND: The objective of this study was to determine the prevalence of presumed ocular tuberculosis among diagnosed pulmonary tuberculosis patients in a tertiary government hospital in the Philippines and determine its common presentation in the population. This was a cross-sectional study in which 103 patients who were labeled to have active pulmonary tuberculosis underwent history and ocular examination prior to anti-tubercular therapy. The diagnosis of presumed ocular tuberculosis was made when clinical signs of tuberculosis (TB) uveitis were found in the participants. Lesions were documented and tallied, after which statistical analysis was performed. RESULTS: Seven out of the 103 pulmonary TB patients (6.8% prevalence: 95% CI 2.78% to 13.5%) included in the study showed signs of ocular inflammation. There was no sex and age predilection between those with presumed ocular TB and those without. Posterior uveitis alone was observed in three of the patients (two cases of retinal vasculitis and one case of choroidal tubercle). Non-granulomatous anterior uveitis with posterior synechiae alone was observed in two patients. One patient had combined non-granulomatous anterior uveitis with posterior synechiae and choroidal tubercle. One had combined granulomatous anterior uveitis with posterior synechiae and choroidal tubercle. Intermediate uveitis was not noted among the patients. CONCLUSIONS: Presumed ocular tuberculosis should be considered among patients with diagnosed pulmonary tuberculosis. Common ocular lesions found in the study include choroidal tubercle and non-granulomatous anterior uveitis with posterior synechiae.